RASIO KEUANGAN DALAM MEMPREDIKSI KEBANGKRUTAN PERUSAHAAN PERTAMBANGAN BATUBARA - Sidabalok, Eva Lisnawati; Deviyanti, Dwi Risma; Ginting, Yoremia Lestari (EQUITY, 2017)
The purpose of this study was to analyzed how much influence the return on assets (ROA), current ratio (CR), and debt ratio (DR) to the financial distress of coal mining companies listed in Indonesian Stock Exchange the period of 2010 – 2015. This study used secondary data obtained from IDX website with data collection method of purposive sampling then obtained 35 data sample research. Method of data analysis in this research is multiple linear regression analysis. Result of this research is return on assets (ROA) have significant positive effect to financial distress, current ratio (CR) has no positive significant effect on financialdistress, and debt ratio (DR) has a significant negative effect on financial distress of coal mining company. The results of this study obtained R square value of 0.869 which means the company’s financial distress condition can be predicted by using the four independent variabels.